2020
DOI: 10.2217/rme-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Regenerative Cells Improve Implantation of Fertilized Eggs in Thin Endometrium

Abstract: Aim: Embryo implantation and subsequent pregnancy depends on endometrial thickness. To investigate potential fertility strategies for women with thin endometrium, we explored the efficacy of adipose tissue-derived regenerative cells (ADRCs) on thin endometrium and embryo implantation in a mouse model. Materials & methods: ADRCs isolated from mouse subcutaneous fat were characterized by flow cytometry. Endometrium thickness, endometrial fibrosis, embryo implantation and angiogenesis factors were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…In the AS and EA, the thickness of Endometrium increased approximately from 4.3 mm to 6.7 mm [ 48 ] menSCs Jichun Tan et al Human The transplantation of Autologous menSCs considerably rise endometrial thickness (ET) for women with severe AS [ 49 ] hESP cells Irene Cervelló et al Human The mesenchymal origin of hESP confirmed by their ability to differentiate in vitro into osteocytes and adipocytes. Eventually, after transplanted under renal capsule of NOD-SCID mice they have displayed the potency to generate human endometrium [ 50 ] Autologous adipose derived stem cells (ADSCs) Sudoma et al Human ADSCs subendometrial introduction led to endometrial thickness increase, 13 pregnancies occurred and 9 healthy babies were born [ 51 ] uterus derived mesenchymal stem cells and their exosomes Saribas et al Rat It was shown that proliferation and vascularization increased and fibrosis decreased in uterus as a result of MSC and exosome treatments [ 52 ] Autologous bone marrow-derived stem cell Singh et al Human Intrauterine stem cell treatment is a promising novel approach for refractory cases of AS and EA [ 53 ] Autologous adipose derived stem cells (ADSCs) Yotsumoto et al Mice ADSCs may be a useful therapeutic strategy to improve fertility of women with thin endometrium [ 54 ] Human amniotic epithelial cells (hAEC) Human amniotic epithelial cells (hAEC) Song et al Rat This study revealed that hESCs along with collagen scaffolds could notably support function recovery and uterine repair in a rat model of intense uterine injury [ 55 ...…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…In the AS and EA, the thickness of Endometrium increased approximately from 4.3 mm to 6.7 mm [ 48 ] menSCs Jichun Tan et al Human The transplantation of Autologous menSCs considerably rise endometrial thickness (ET) for women with severe AS [ 49 ] hESP cells Irene Cervelló et al Human The mesenchymal origin of hESP confirmed by their ability to differentiate in vitro into osteocytes and adipocytes. Eventually, after transplanted under renal capsule of NOD-SCID mice they have displayed the potency to generate human endometrium [ 50 ] Autologous adipose derived stem cells (ADSCs) Sudoma et al Human ADSCs subendometrial introduction led to endometrial thickness increase, 13 pregnancies occurred and 9 healthy babies were born [ 51 ] uterus derived mesenchymal stem cells and their exosomes Saribas et al Rat It was shown that proliferation and vascularization increased and fibrosis decreased in uterus as a result of MSC and exosome treatments [ 52 ] Autologous bone marrow-derived stem cell Singh et al Human Intrauterine stem cell treatment is a promising novel approach for refractory cases of AS and EA [ 53 ] Autologous adipose derived stem cells (ADSCs) Yotsumoto et al Mice ADSCs may be a useful therapeutic strategy to improve fertility of women with thin endometrium [ 54 ] Human amniotic epithelial cells (hAEC) Human amniotic epithelial cells (hAEC) Song et al Rat This study revealed that hESCs along with collagen scaffolds could notably support function recovery and uterine repair in a rat model of intense uterine injury [ 55 ...…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…We isolated ADRCs from the subcutaneous adipose tissues of BALB/c female mice and the KuO-expressing transgenic C57BL/6 mouse, as described previously 50 . ADRCs are almost identical to the stromal vascular fraction.…”
Section: Methodsmentioning
confidence: 99%
“…FMC003; R&D Systems). Flow cytometry was performed as described previously [35]. For histological staining, the collected tissues were formalin-xed and then para n-embedded.…”
Section: Flow Cytometric Pathological and Immunohistochemical Analysesmentioning
confidence: 99%
“…We isolated ADRCs from the subcutaneous adipose tissues of BALB/c female mice and the KuOexpressing transgenic C57BL/6 mouse, as described previously [35]. ADRCs are almost identical to the stromal vascular fraction.…”
Section: Isolation Of Adipose-derived Regenerative Cells (Adrcs) and Ascsmentioning
confidence: 99%